REPRESENTATION OF WOMEN CLIMBER IN STUDENT ASSOCIATION FOR ENVIRONMENTAL AND ADVENTURE ACTIVITY - Suryanto, Bradhiansyah Tri; Sari, Andini Krisna (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
This study aims to reveal the position of women climbers in the student association for Environmental and adventure activity of MAPALA Marabunta of Panca Marga University of Probolinggo. This study was conducted by using the method of descriptive qualitative with data collection techniques through observation, interview, and documentation.  The results showed that in mountain climbing activities made by women climbers there is no difference between male and female climbers. This is in a manner conforming to representation view. Women climbers already have the ability and skills to Mountain climbing. The women climber is also equivalent to male climbers in general. So there are no points or ways in which male and female climbers are dissimilar. What distinguishes only their will, whether they want to practice and learn, if they want to practice and learn and take the opportunity already given, it will happen what is on want that is equality.